Online Learning Management During the Covid 19 Period (Descriptive Study At 5 Elementary Schools In Karawang Regency) - Fauziah, Sifa; King Muttaqien, King; Koswara, Nandang (International Journal of Educational Research & Social Sciences, 2022)
The research in the form of a dissertation is entitled "Educational Management of Principals in Implementing On-Line Learning Policies (Descriptive Studies at SDN in Karawang Regency). The purpose of this study was to determine: 1) Online learning education management implemented by the principal at SDN Karawang Regency; 2) Obstacles faced in the online teaching and learning process at SDN Karawang Regency; 3) How can the national education goals be achieved through online teaching and learning processes at SDN Karawang Regency; 4) The efforts of educators to carry out the online teaching and learning process at SDN Karawang Regency. The method used is a qualitative method to determine the education management process of school principals in implementing online learning policies. The results of this study are: 1) the education management of school principals in implementing online learning policies refers to Permendikbud No. 24 / 2014 concerning Distance Education, Permendikbud No.109 / 2013 concerning PJJ, Permendikbud No. 119 / 2014, Permenristekdikti No. 50 / 2015 concerning PJJ and E-Learning, Circular Letter No. 15 / 2020 concerning Guidelines for Organizing Learning from Home in an Emergency Period The spread of Corona Virus Disease (Covid 19), both in planning, implementing, organizing and evaluating. However, in its implementation there are still difficulties considering the uncertainty of when the Covid 19 disaster will end and the lack of experience of human resources for teachers and students in the online learning process that is in accordance with the standards of the education process; 2) Obstacles faced include, among other things, students only play and do not study seriously, students are still difficult to learn independently, lack of interaction that can motivate students in learning, the presence of teachers infected with Covid 19 has an impact on the concerns of parents of students being infected. their sons and daughters, teachers do not all understand using online platforms that can support online learning activities, teachers only use conventional methods, namely by giving assignments to students, there is no internet quota, students do not have gadgets (mobile phones), unpreparedness of parents in buying internet quota, parents of students who do not understand the learning materials of students and the ability to master technology, lack of internet signal or weak internet signal; 3) The goal of national education through online teaching and learning at SDN Karawang Regency based on government policies has not been fully achieved; 4) Efforts made by educators at SDN in Karawang Regency in the online learning process still make students the object of an Education project.